Fabrication and characterization of graphene/AlGaN/GaN ultraviolet Schottky photodetector. (7th June 2016) - Kumar, M; Jeong, H; Polat, K; Okyay, A K; Lee, D
Abstract: We report on the fabrication and characterization of a Schottky ultraviolet graphene/AlGaN/GaN photodetector (PD). The fabricated device clearly exhibits rectification behaviour, indicating that the Schottky barrier is formed between the AlGaN and the mechanically transferred graphene. The Schottky parameters are evaluated using an equivalent circuit with two diodes connected back-to-back in series. The PD shows a low dark current of 4.77  ×  10 −12 A at a bias voltage of  −2.5 V. The room temperature current–voltage ( I – V ) measurements of the graphene/AlGaN/GaN Schottky PD exhibit a large photo-to-dark contrast ratio of more than four orders of magnitude. Furthermore, the device shows peak responsivity at a wavelength of 350 nm, corresponding to GaN band edge and a small hump at 300 nm associated to the AlGaN band edge. In addition, we examine the behaviour of Schottky PDs with responsivities of 0.56 and 0.079 A W −1 at 300 and 350 nm, respectively, at room temperature.